Magnetoelectric core-shell nanoparticles for nervous tissue electrostimulation: Performance in In vitro and ex vivo organotypic cultures - Gulino, Maurizio; Kim, Donghoon; Tang, Qiao; Sevim, Semih; Zhang, Elric; Ye, Hao; Chen, Xiang-Zhong; Morais, Miguel Rafael Gonçalves; Santos, Sofia Duque; Pané, Salvador; Pêgo, Ana Paula (Acta biomaterialia, 2025)
This work presents functional multiferroic cobalt ferrite-based nanoparticles (CFO NPs) coated with calcium/zirconium-doped barium titanate (CFO-BCZT) that demonstrate notable magnetoelectric coupling and biocompatibility for neural applications. The core-shell structure was synthesized through hydrothermal and sol-gel processes. Uncoated CFO NPs and CFO NPs coated with bismuth ferrite (CFO-BFO) were used for comparison. X-ray diffraction revealed cubic CFO core and tetragonal BCZT shell without any secondary phase, nor impurities. Magnetoelectric coupling effect of CFO-BCZT MENPs was revealed through piezoresponse force microscopy. Biological cellular responses to CFO-BCZT MENPs were evaluated through cytotoxicity assays, microscopy analysis, and cellular uptake on primary neurons, astrocytes or microglia cultures. Long-term effects were studied in rodent 3D organotypic hippocampal cultures. Moreover, the magnetoelectric performance of CFO-BCZT and CFO-BFO MENPs was assessed in vitro with SH-SY5Y human neuronal cell lines under magnetic stimulation. The results showed CFO-BCZT MENPs superior biocompatibility both in vitro and ex vivo in organotypic brain slices, while CFO-BFO MENPs reduced microglial viability and induced inflammatory changes. Additionally, tissue penetration of CFO-BCZT MENPs through magnetic attraction was successfully achieved on organotypic hippocampal cultures, without causing either cell damage or disruption of neural connections. Finally, SH-SY5Y neuronal cell line showed good neurite outgrowth with the tested magnetic stimulation parameters. In conclusion, CFO-BCZT MENPs not only exhibited a magnetoelectric coupling effect but also greater biocompatibility compared to CFO-BFO and uncoated CFO NPs, positioning them as promising composite materials for brain stimulation therapies. STATEMENT OF SIGNIFICANCE: Magnetoelectric nanoparticles are emerging as promising tools for non-invasive brain stimulation therapies. Our work introduces biocompatible multiferroic cobalt ferrite- based nanoparticles (CFO NPs) coated with calcium/zirconium-doped barium titanate (CFO-BCZT) as candidate materials for neural applications, representing a combination of cobalt ferrite cores with calcium/zirconium-doped barium titanate shells. These core-shell nanostructures exhibit strong magnetoelectric coupling and significantly improved biocompatibility compared to conventional alternatives, such as bismuth ferrite coatings. Their ability to penetrate brain tissue through magnetic attraction without inducing cellular toxicity or inflammation on ex vivo organotypic hippocampal slices, while promoting neurite outgrowth on in vitro neuronal cell cultures, positions them as promising tools for non-invasive neural modulation. This study paves the way for safe, wireless brain stimulation platforms using multifunctional nanomaterials.